Artemis III EVA Opportunities in the Vicinity of the Lunar South Pole on the Rim of Shackleton Crater - Kring, David A. (David Allen); Barrett, Natasha; Boazman, Sarah; Gawronska, Aleksandra; Gilmour, Cosette; Halim, Samuel; Harish; McCanaan, Kathryn; Satyakumar, Animireddi V.; Shah, Jahnavi; orcid:0000-0003-3150-6787; orcid:0000-0002-3440-6282; et al. (2020)
EVAs in this location can begin to address science objectives 1c, 2a, 3a, 3b, 3d, 4a, 4d, 6c, and 7b, and potentially address objectives 1a, 1b, 4b, 5a-b, and 7d [9]. EVAs can also help address strategic knowledge gaps (SKGs) I-D, I-G, II-D-3, III-C-2, III-D-1, III-D-2, III-D-4, and III-J-4 of Context for Exploration of the Moon. National Academies Press, Washington D. C. David A. Kring, Natasha Barrett, Sarah J. Boazman, Aleksandra Gawronska, Cosette M. Gilmour, Samuel H. Halim, Harish, Katie McCanaan, Animireddi V. Satyakumar, and Jahnavi Shah